Simulation of hydrodynamic condictions at santa marta coastal area (colombia) (2012)
Hydrodynamic conditions of the Santa Marta coastal area were determined, using a 3D hydrodynamic model. RMA10 model was previously calibrated and validated for two different periods in the year (dry season and rainy season). A good approach between measures and simulations was found. For the year 2001, the model predicted current magnitude and current velocity at 40 meters deep in the water column. Maximum current magnitude of 12 cm/s was found. Current magnitude distribution showed 30% for the range between 2 and 4 cm/s, and for the range between 4 and 6 cm/s. The main axis of current was 62-242 degrees.